2013
DOI: 10.3109/07357907.2013.840383
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of an Enzyme Prodrug Therapy Targeted to the Breast Tumor Vasculature

Abstract: The L-methioninase-annexin V/selenomethionine enzyme prodrug system, designed to target the tumor vasculature and release the methylselenol anticancer drug in the tumor, was tested in mice with implanted MBA-MB-231 breast tumors. This therapy was able to cause a reduction in the size of the tumors during the treatment period. It was shown that L-methioninase-annexin V was uniformly bound at the blood vessel surface in the tumor and also that there was a substantial cutoff of blood flowing through the treated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Cytotoxic efficacy of our FP systems on HAAE-1 cells has also been demonstrated previously in vitro, with cell killing ranging from 5-100% [23]–[25]. We have validated these in vitro methods for determining vascular targeting/cytotoxic efficacy via the successful transition of the MT-AV/SeMet system in vivo for mice with implanted MDA-MB-231 breast tumors [38]. …”
Section: Introductionsupporting
confidence: 55%
“…Cytotoxic efficacy of our FP systems on HAAE-1 cells has also been demonstrated previously in vitro, with cell killing ranging from 5-100% [23]–[25]. We have validated these in vitro methods for determining vascular targeting/cytotoxic efficacy via the successful transition of the MT-AV/SeMet system in vivo for mice with implanted MDA-MB-231 breast tumors [38]. …”
Section: Introductionsupporting
confidence: 55%
“…The key characteristics of targeted enzymes are their biodistribution and pharmacokinetic properties. These enzymes should exhibit a high uptake level at the tumor site, and should degrade rapidly in the blood and normal tissues, converting the prodrugs in a site-specific manner (2,3,24,25). Therefore, it is important to investigate the in vivo distribution and clearance mechanisms of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic agent can be precisely released at tumor site which can avoid systemic toxicity, and can diffuse into adjacent cells making the non-antigen expressed tumor cells undergo treatment [4], which can further improve the treatment. The enzymes used in this strategy have relatively fixed relations with prodrugs, such as carboxypeptidase G2 and benzoic mustard [5], nitroreductase and CB1954 [6,7], l -methioninase and selenomethionine [8,9], cytosine deaminase and 5-fluorocytosine [9,10], β-lactamase and cephalosporin prodrugs [11,12]. In the previous study we constructed a conjugate (RGD4CβL) of RGD4C (ACDCRGDCFCG) and β-lactamase variant with low immunogenicity for use in the enzyme prodrug therapy, in which the RGD4C motif served as direct group for its specificity to α v β 3 integrin which is overexpressed on tumor cells and is usability for incorporation into proteins by recombinant technology [13,14,15], and studies showed the fusion protein not only retains catalytic activity of β-lactamase but has low immunogenicity and high stability [16,17].…”
Section: Introductionmentioning
confidence: 99%